Acute and sub-acute toxicity evaluation of dihydro-p-coumaric acid isolated from leaves of Tithonia diversifolia Hemsl. A. Gray in BALB/c mice - Devi, Thiyam B.; Jena, Sarita; Patra, Biswajit; Singh, Kabrambam D.; Chawla, Saurabh; Raina, Vishakha; Koijam, Arunkumar Singh; Parida, Ajay; Rajashekar, Yallappa (Frontiers in Pharmacology, 2022)
In present study, the acute and sub-acute toxicities of dihydro-p-coumaric acid isolated from the leaves of Tithonia diversifolia (Hemsl.) A. Gray was studied for safety issues in mammals. For acute toxicity tests, isolated compound was administered orally in both male and female BALB/c mice at the doses of 200, 800 and 1600 mg/kg body weight for 7 days. In sub-acute toxicity study 50 and 500 mg/kg bw of the compound was orally administered for 14 days. Toxicity induced behavioural changes, haematological parameters, biochemical markers and histopathological sections were studied after Dihydro-p-coumaric acid administration. The vital organs like heart, kidney, uterus and testis revealed no adverse effects at doses of upto 1600 mg/kg bw and 500 mg/kg bw. Slight hepatotoxicity was however demonstrated by ALT and AST assay but histopathological section did not concur as much. The study demonstrated insignificant difference in the percentage of feed intake, water intake, weight gain, haematological parameters and histopathological changes, with no toxicity signs and mortality. Dihydro-p-coumaric acid can be regarded as safe in both acute and sub-acute toxicity assay in both sexes. This indicates dihydro-p-coumaric acid as a viable alternative to synthetic pesticides.